Incentive mechanisms and HRM practices in China: A comparison between state-owned and private enterprises - Yuan, Yidan (2022)
Today, with globalization gaining momentum and competition becoming increasingly fierce, the challenges faced by Chinese enterprises are enormous. In order to survive and grow, enterprises must organize and fully utilize their human, material and financial resources in an efficient manner, therefore, one of the most challenging tasks in the management of human resources is the establishment and implementation of employee motivation mechanisms. Over the past few decades, motivation theory and motivational mechanisms have been studied by many scholars both at home and abroad. However, there have been few comparative studies on Chinese state-owned enterprises and privately-owned enterprises. The aim of this dissertation is to compare and analyse two different types of enterprises in China. A qualitative research approach is adopted. This dissertation poses a series of research questions to understand the current incentives of SOEs and POEs in China, the similarities and differences between them both, and the causes and effects of the similarities and differences. The 12 interviewees involved in this study were current employees from two SOEs and two private companies. The results of the interviews were analysed and discussed through a combination of relevant literature and background research. Finally, the reasons, possible implications and recommendations are presented.